On the occurrence of elementary abelian $p$-groups as the Schur multiplier of non-abelian $p$-groups - Rai, Pradeep K. (Comptes Rendus. Mathématique)
We prove that every elementary abelian $p$-group, for odd primes $p$, occurs as the Schur multiplier of some non-abelian finite $p$-group.